2005
DOI: 10.1136/jnnp.2004.038414
|View full text |Cite
|
Sign up to set email alerts
|

The - 148 C/T fibrinogen gene polymorphism and fibrinogen levels in ischaemic stroke: a case-control study

Abstract: Background: To determine whether 2148 C/T fibrinogen gene promoter polymorphism increases stroke risk by modifying the fibrinogen level. Design: A case-control study of patients with first ever ischaemic stroke, confirmed by computed tomography. Methods: Venous blood samples were collected for fibrinogen and routine coagulation tests one week after the stroke, and after three months in about half the patients. Population controls were age and sex matched. 2148 C/T fibrinogen polymorphism was determined by poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
(23 reference statements)
1
16
1
Order By: Relevance
“…Consistent with what has previously been reported, we found a strong correlation between fibrinogen and CRP concentration [29], a decrease in fibrinogen concentration during follow-up [5,17,20], and an association between acute plasma fibrinogen and stroke severity [20,29]. This may suggest that increased plasma fibrinogen in stroke merely reflects an inflammatory response to the event.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with what has previously been reported, we found a strong correlation between fibrinogen and CRP concentration [29], a decrease in fibrinogen concentration during follow-up [5,17,20], and an association between acute plasma fibrinogen and stroke severity [20,29]. This may suggest that increased plasma fibrinogen in stroke merely reflects an inflammatory response to the event.…”
Section: Discussionsupporting
confidence: 90%
“…Results indicate that the FGA and FGG genes may be of importance [13,14]. In contrast, several studies have investigated the possible association between fibrinogen gene polymorphisms, plasma fibrinogen level, and ischemic stroke, as well as coronary heart disease [15][16][17][18][19][20][21][22]. Although many studies have reported an association between FGB gene polymorphism and plasma fibrinogen, results have been inconsistent with respect to cardiovascular and cerebrovascular events [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study design has been described previously. 6 Baseline characteristics are given in Table 1. Blood was collected from an unselected subgroup of 47 patients 7 to 14 days (acute phase) and 3 months after the stroke in tubes containing 1/10 volume of 0.129 mol/L sodium citrate.…”
Section: Methodsmentioning
confidence: 99%
“…20 These include animal studies suggesting that fibrinogen has an intrinsically central nervous system toxicity, 21 promoting apoptosis, 22 neurodegeneration 23 and an inhibition of functional recovery after injury. 24 High fibrinogen concentrations provide additional information about risk, even if it is simply a bystander of the inflammatory response in ischemic stroke and transient ischemic attack.…”
Section: Why? Evidence Regarding the Association Of Fibrinogen And Ismentioning
confidence: 99%